Effects of density and microstructure on surface integrity of HIP materials. (9th October 2019) - Sun, F.J.; Qu, S.G.; Su, F.; Deng, Z.H.
Ti-6Al-4V materials with different densities were prepared using hot isostatic pressing (HIP) technology. Surface integrities of the HIP materials were studied to analyse the surface integrity changing trend with density and microstructure. Due to the existence of micro-voids of the HIP material micro-hole appeared in the machined workpiece surface, which resulted in the formation of the deeper and greater micro-hole defects with decreasing material density. The serrated chip formation, different nanoindentation hardness of crystalline structures and micro-void existence had a potential to make the plastic deformation of the workpiece surface layer along the cutting direction to be different. Refined β phase and micro-void greatly affected plastic deformation of the workpiece surface layer, and the residual tensile stress was influenced by the microstructure and residual micro-void in machining of the HIP materials prepared with different HIP parameters.